Negotiating Difference: Sunni–Shia Relations and Grassroots Religious Moderation in Jepara, Indonesia - Rosyid, Moh; Kushidayati, Lina (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study examines the dynamics of religious moderation between Sunni and Shia Muslims in Jepara City, Central Java, highlighting the unique context of Shia as a minority facing significant challenges in Indonesia. The research addresses four primary questions: the nature of Sunni resistance to Shia, the manifestations of religious moderation in Jepara, the teachings that threaten Sunni-Shia coexistence, and the impact of Sunni understanding on their attitudes towards Shia across Indonesia. Data gathered through interviews, observations, and literature reviews in 2024 reveal a historical backdrop of Sunni resistance to Shia, including political struggles, persecution, and the issuing of fatwas. Despite this, the study underscores a notable absence of conflict in Jepara since the 1980s, when a culture of moderation emerged. However, concerns remain regarding the potential for immoderation due to doctrinal differences. Initial findings indicate that, while Sunni citizens may refrain from attending Shia activities involving internal Shia doctrine, they are open to participating in non-doctrinal events, suggesting a complex interplay of acceptance and resistance within the community.